From Mission to Competition: The Experiences of 10 LDS Missionary Student-Athletes Returning to Competition in the National Collegiate Athletic Association Division I - Matthew J. Moore; Leslee A. Fisher; Lindsey A. Miossi; Zach T. Smith; Jacob C Jensen (Movement and Being: The Journal of the Christian Society for Kinesiology, Leisure and Sports Studies, 2022)
The purpose of the current study was to explore the experiences of LDS missionary student-athletes returning to competition in the National Collegiate Athletic Association (NCAA) Division I (DI). Using Consensual Qualitative Research methods (CQR; Hill, 2012) including a semi-structured interview guide, 10 DI student-athletes/returned LDS missionaries were interviewed regarding their experience (i.e., mean age of 25 years; baseball, cross-country/track and field, football, and swimming). A research team with five members constructed four domains and 16 categories representing DI student-athlete/returned LDS missionary chronological identity changes during this experience: (a) the development of an LDS missionary identity; (b) challenges associated with returning to DI student-athlete identity; (c) benefits of mission identity on DI student-athlete identity; and (d) practical implications for sport psychology professionals and other support staff. Suggestions for future research are also given.
Keywords: The Church of Jesus Christ Latter-day Saints; NCAA; sport psychology; spirituality; consensual qualitative research